Studi Transmedia Storytelling pada Karakter Mili Kecil dalam 2 Buku Ilustrasi Anak (Mili Kecil dan Pemilik Paket Misterius & Mili Kecil dan Temannya yang Berapi-api) - Aditia Muara Padiatra; Suci Nofita Sari (UIN Siber Syekh Nurjati Cirebon, 2025)
This article discusses the transmedia storytelling process of Mili Kecil character in 2 (two) children's illustrated books. In this case, the transmedia approach is used to analyze the expansion of the character, from previously being a child in the real world to becoming a fictional character. The theoretical framework focuses on transmedia storytelling in the scope of character studies. The methodological approach is based on the transmedia character analysis model developed by Kunz and Wilde (2023). The research findings show that the transmedia strategy is seen in the character Mili Kecil, who in this case always appears and becomes the central point in the narration of the story in the two children's illustrated books. Furthermore, Mili Kecil's characteristic as a cheerful girl with curly hair and sunflowers, which is a marker of transmedial identity, always consistently appears in every story. On the other hand, instead of just following the storyline in this case, readers are also invited to take part in Mili's adventures through narratives presented as part of the subjective representation of Mili Kecil's character, although the limited target readership in author's opinion influences the expansion of Mili Kecil's emotional stance as a transmedial character.